2019
DOI: 10.2514/1.a34069
|View full text |Cite
|
Sign up to set email alerts
|

Drag Behavior of Inflatable Reentry Vehicle in Transonic Regime

Abstract: The drag coefficient for inflatable reentry vehicles shows discrepancies between a wind tunnel experiment and a flight test in a transonic regime. These discrepancies exist in the drag decrease behavior in the transonic regime and local minimum values of drag above the sonic speed in a wind tunnel. Hence, the present paper focuses on uncovering the reasons and mechanisms behind the same and investigates transonic flow fields around a vehicle by using a transonic wind tunnel and the computational fluid dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…There was an obvious expansion wave that appeared in front of the IAD (Figure 4(a)) at Ma = 1, while an obvious bow shock appeared in front of the IAD (Figure 4(b-c)) when the Ma was 3 and 4.5. These were consistent with the wind tunnel experimental results in the literature [12]. With the increase of the cone angle, the pressure of the external flow field increased slightly at Ma = 1 (Figures 4 (b)(e)(f)) and changed nonlinearly.…”
Section: Different Ma Flight Conditions (Aoa = 0)supporting
confidence: 91%
See 1 more Smart Citation
“…There was an obvious expansion wave that appeared in front of the IAD (Figure 4(a)) at Ma = 1, while an obvious bow shock appeared in front of the IAD (Figure 4(b-c)) when the Ma was 3 and 4.5. These were consistent with the wind tunnel experimental results in the literature [12]. With the increase of the cone angle, the pressure of the external flow field increased slightly at Ma = 1 (Figures 4 (b)(e)(f)) and changed nonlinearly.…”
Section: Different Ma Flight Conditions (Aoa = 0)supporting
confidence: 91%
“…The results showed that the drag of the IAD had a significant relationship with its cone angle, and the shape of the IAD would have an influence on the aerodynamic characteristics. Takahashi [12] studied the aerodynamic coefficients of the IAD by transonic wind tunnel experiment and CFD and obtained the mechanism of differences between the above two methods and flight experiments. The results showed that the leeward of the test model affected the drag at the transonic and supersonic regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Aimed at these defects, the inflatable reentry vehicle experiment (IRVE) is becoming an emerging technology [1,2]. However, the safety problems of the thermal protection system (TPS) and flexible inflation toroids under hypersonic flow are serious [3,4]. The aerodynamic force will make large deformation and dynamic stress of flexible film [5], and the aeroheating will not only increase the surface temperature of TPS but also induce the thermal expansion of inflation gas [6].…”
Section: Introductionmentioning
confidence: 99%